2010
DOI: 10.1002/jcu.20727
|View full text |Cite
|
Sign up to set email alerts
|

Ectopia cordis in a fetus with mosaic trisomy 16

Abstract: Ectopia cordis and mosaic trisomy 16 are two rare fetal anomalies, which have not been reported in association. We report a case of an isolated ectopia cordis at 11+3 weeks. Subsequent embryological examination confirmed thoracic ectopia cordis with normal heart structure and array comparative genomic hybridization of fetal tissue detected trisomy 16 mosaicism. © 2010 Wiley Periodicals, Inc. J Clin Ultrasound 38:386‐388, 2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Ectopia cordis is a rare congenital anomaly that occurs with an incidence of 5.5 to 7.9 per million live births. 1,4 Around the fourth week of gestation, the embryonic disc goes through the process of gastrulation and neurulation, forming a tube-like structure consisting of three germ cell layers: ectoderm, endoderm, and mesoderm. 5,6 The endoderm and mesoderm ultimately form the gut tube and body wall, which if it fails to close properly results in a ventral wall defect such as ectopia cordis, gastroschisis, omphalocele, bladder, or cloacal exstrophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ectopia cordis is a rare congenital anomaly that occurs with an incidence of 5.5 to 7.9 per million live births. 1,4 Around the fourth week of gestation, the embryonic disc goes through the process of gastrulation and neurulation, forming a tube-like structure consisting of three germ cell layers: ectoderm, endoderm, and mesoderm. 5,6 The endoderm and mesoderm ultimately form the gut tube and body wall, which if it fails to close properly results in a ventral wall defect such as ectopia cordis, gastroschisis, omphalocele, bladder, or cloacal exstrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopia cordis is defined as partial or complete displacement of the heart outside of the thoracic cavity. 1 It may be an isolated malformation or associated with ventral wall defects that affect the thorax or abdomen. 1,2 In some cases, ectopia cordis is thought to be the result of amniotic band syndrome, in which strands of the amnion adhere to the fetus, resulting in an open defect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EC can be associated with chromosomal anomalies, especially trisomy 18 and Turner syndrome, and genetic syndromes [18]. Previous studies have reported the association with triploidy 69, XXY [19], mosaic trisomy 16 [20] and 46, XX,17q+ [21]. Due to the higher risk of such association, analysis of the karyotype is highly recommended.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…In cattle and humans, no environmental causes have been described for this condition. In the literature, it has often been suggested that in humans, ectopia cordis may be the result of unbalanced chromosomal defects, such as mosaic trisomy 16, trisomy 18 and sex chromosome abnormalities (King, 1980;Shaw et al, 2006;Arnaoutoglou et al, 2010;Diaz-Serani and Sepulveda, 2020), although this is not always the case (King, 1980). In calves, only a limited number of ectopia cordis cases have been genetically investigated and were shown to be associated with the presence of extra chromosome material represented under the form of a marker chromosome (Windberger et al, 1992).…”
Section: Introductionmentioning
confidence: 99%